Does Chemistry Content in a State Electronic Library Meet the Needs of Smaller Academic Institutions and Companies? - Meghan Lafferty (Issues in Science and Technology Librarianship, 2008)
Smaller academic institutions and companies are not always able to afford access to Chemical Abstracts, the major source for the chemical literature, via SciFinder, SciFinder Scholar, or STN. In Minnesota, as in many other states, citizens do have access to a suite of interdisciplinary databases that offer some coverage of the chemical literature. I examined the coverage dates, document types, full-text availability, impact factor, publishers, and searchability and indexing of the chemistry-related content of Academic Search Premier and Business Source Premier which index academic and trade publications. A number of key journals in the field are indexed in the databases, but coverage does not go back very far. For this reason, I would not recommend it for undergraduates. The length of coverage may not be as important in industry as their needs are different. [ABSTRACT FROM AUTHOR]